Implementation of Xpert MTB/RIF in 22 high tuberculosis burden countries: are we making progress?. Issue 2 (31st August 2017) - Cazabon, Danielle; Suresh, Anita; Oghor, Collins; Qin, Zhi Zhen; Kik, Sandra V.; Denkinger, Claudia M.; Pai, Madhukar
By the end of 2016, approximately 23 million Xpert MTB/RIF ® (Xpert; Cepheid, Sunnyvale, CA, USA) cartridges for tuberculosis (TB) diagnosis had been procured by the public sector in 130 countries at concessional pricing [1], but smear microscopy continues to be the most widely used test for TB [2]. To understand the true market penetration of Xpert in TB high burden countries (HBCs), we surveyed National TB Programmes (NTPs) or their partnering organisations in 22 HBCs to obtain Xpert data from 2015 and to assess dynamic trends from 2014 to 2015. These 22 countries had been previously surveyed by us in 2014 [3]. Uptake of Xpert in 22 high burden countries has progressed well since 2014, although more can be done to reach scale http://ow.ly/Whvu30dpqVI